2020
DOI: 10.1098/rsif.2020.0474
|View full text |Cite
|
Sign up to set email alerts
|

Endoskeletal mineralization in chimaera and a comparative guide to tessellated cartilage in chondrichthyan fishes (sharks, rays and chimaera)

Abstract: An accepted uniting character of modern cartilaginous fishes (sharks, rays, chimaera) is the presence of a mineralized, skeletal crust, tiled by numerous minute plates called tesserae. Tesserae have, however, never been demonstrated in modern chimaera and it is debated whether the skeleton mineralizes at all. We show for the first time that tessellated cartilage was not lost in chimaera, as has been previously postulated, and is in many ways similar to that of sharks and rays. Tesserae in Chimaera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 96 publications
(295 reference statements)
4
41
0
1
Order By: Relevance
“…Previous studies showed poorly developed cartilaginous tissue in the posterior vertebrae of juvenile H. colliei, where histology displayed no sign of modified cartilaginous matrix that could be linked to cartilage mineralization (Debiais-Thibaud, 2019). However, more recent publications pointed out the thin layer of mineralized matrix in the synarcual of the elephant shark Callorhinchus milii (Pears et al, 2020) and recognized thin tesserae in the adult C. milii and rabbit fishes Chimaera monstrosa (Pears et al, 2020;Seidel et al, 2020). In our H. colliei sample, we detect a similar thin layer of mineralized tissue in the synarcual of a hatchling and a juvenile specimen (Figures 4A,G).…”
Section: Synarcual Mineralization In Hydrolagus Collieisupporting
confidence: 77%
See 2 more Smart Citations
“…Previous studies showed poorly developed cartilaginous tissue in the posterior vertebrae of juvenile H. colliei, where histology displayed no sign of modified cartilaginous matrix that could be linked to cartilage mineralization (Debiais-Thibaud, 2019). However, more recent publications pointed out the thin layer of mineralized matrix in the synarcual of the elephant shark Callorhinchus milii (Pears et al, 2020) and recognized thin tesserae in the adult C. milii and rabbit fishes Chimaera monstrosa (Pears et al, 2020;Seidel et al, 2020). In our H. colliei sample, we detect a similar thin layer of mineralized tissue in the synarcual of a hatchling and a juvenile specimen (Figures 4A,G).…”
Section: Synarcual Mineralization In Hydrolagus Collieisupporting
confidence: 77%
“…More recent studies have reassessed the diversity of poorly described features of mineralization in cartilaginous fishes (Eames et al, 2007;Enault et al, 2015;Seidel et al, 2017Seidel et al, , 2020Atake et al, 2019;Debiais-Thibaud, 2019;Smith et al, 2019;Chaumel et al, 2020;Pears et al, 2020), raising new questions on the origin and evolution of mineralized tissues in this clade and therefore in vertebrates. Comparative studies of skeletal tissues in non-tetrapods have uncovered a wide range of skeletal tissues that had remained unknown from the sole study of tetrapods (discussed by Huysseune, 2009 andHall andWitten, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to contradictory descriptions of chimaeroid tissues (Lund and Grogan, 1997;Grogan and Lund, 2004;Pradel et al, 2009), prompting calls for more research (Eames et al, 2007;Dean et al, 2015;Enault et al, 2016). Notably, recent examination of chimaeroid mineralized skeletal tissues identified tesseral structures in the vertebral column (synarcual) and Meckel's cartilage of Chimaera and Hydrolagus (both Family Chimaeridae; Finarelli and Coates, 2014;Debiais-Thibaud, 2019;Seidel et al, 2019aSeidel et al, , 2020 and in the fin skeleton of Callorhinchus (Family Callorhinchidae; Maisey et al, 2020), seemingly refuting the view that extant chimaeroids lack tessellated cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Hiu dan pari merupakan anggota dari subkelas Elasmobranchii (Dulvy et al 2014;Dharmadi & Satria 2015;SEAFDEC 2017;Hara et al 2018;D'Alberto et al 2019;Bernardo et al 2020), dimana Elasmobranchii mencakup sekelompok besar ikan karnivora dan detritivora yang tersebar di seluruh dunia, mulai dari perairan dangkal hingga kedalaman abisal (Tuya et al 2020). Selain itu, hiu dan pari juga tergolong sebagai anggota kelas Chondrichthyes (Bhat et al 2018;Seidel et al 2020;Jambura et al 2020;Herraiz et al 2020;Sternes & Shimada 2020) yaitu ikan bertulang rawan dari salah satu garis keturunan vertebrata tertua yang paling beragam secara ekologisnya dan muncul lebih dari 420 juta tahun yang lalu (Tiktak et al 2020). Menurut Heithaus et al (2008) dan Ferretti et al (2010) hiu dianggap memainkan peran penting dalam penataan jaring-jaring makanan di laut.…”
Section: Pendahuluanunclassified